2017
DOI: 10.1016/j.eja.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of soil water, soil temperature, and plant roots in a drip-irrigated intercropping field with plastic mulch

Abstract: a b s t r a c tIntercropping and drip irrigation with plastic mulch are two agricultural practices used worldwide. Coupling of these two practices may further increase crop yields and land and water use efficiencies when an optimal spatial distribution of soil water contents (SWC), soil temperatures, and plant roots is achieved. However, this coupling causes the distribution of SWCs, soil temperatures, and plant roots to be more complex than when only one of these agricultural practices are used. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 37 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…The soil temperatures between the P1 and P3 treatments were similar, although the average soil temperature for the P1 treatment was 0.1-0.7 o C higher than for the P3 treatment (Fig.8). Li et al (2017) also reported small soil temperature differences in different irrigation treatments. The soil temperature for the P2 treatment was the lowest among the three treatments.…”
Section: Soil Temperature Transport and Distributionmentioning
confidence: 89%
“…The soil temperatures between the P1 and P3 treatments were similar, although the average soil temperature for the P1 treatment was 0.1-0.7 o C higher than for the P3 treatment (Fig.8). Li et al (2017) also reported small soil temperature differences in different irrigation treatments. The soil temperature for the P2 treatment was the lowest among the three treatments.…”
Section: Soil Temperature Transport and Distributionmentioning
confidence: 89%
“…Root samples for corn and tomatoes under good growth conditions were collected from a soil transect using a method of Li et al (2017) during the elongation stage (June 12 and 8 in 2014 and 2015, respectively), the tasseling stage (June 25 and 18 in 2014 and 2015, respectively), the filling stage (July 11 and 18 in 2014 and 2015, respectively), and the maturation stage (August 20 and 23 in 2014 and 2015, respectively). These samples were collected every 5 cm down to a depth of 50 cm where higher roots density occurred, and then every 10 cm below the 50-cm depth until no roots were found.…”
Section: Measurements and Methodsmentioning
confidence: 99%
“…For example, the results of an experiment in a corn/soybean intercropping ecosystem under full irrigation indicated that the corn roots not only penetrated deeper than those of soybean but also extended into the soybean part of the field to absorb more resources (Gao et al, 2010). Similarly, there were significant differences in the crop root systems in the tomato/corn intercropping ecosystem during the growing season, while the crop root systems of the two species overlapped and competed for soil water and nitrogen (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are great differences in root system distribution in the different growth stages of cotton [39]. These differences will result in differences in root water uptake [38], leading to differences in soil water content distribution with horizontal location and soil depth [40].…”
Section: Effects Of Soil Water Distribution On Soil Salt Distributionmentioning
confidence: 99%